A PROSPECTIVE CLINICALTRIAL OF AMLODIPINE IN COMPARISON TO PERINDOPRIL - Das, Suprava; Thuwin, Myat Thu; G., Sherly Deborah; ., Lubnashirin; Kabir, Mohammad Shahjahan; Chigurupati, Sridevi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of this research was to perform a prospective clinical trial to compare antihypertensive effects of amlodipine and perindopril in hypertensive patients. Methods: In our study, we compared antihypertensive effects of well tolerated and commonly used antihypertensive drugs, amlodipine and perindopril. There were 81 hypertensive patients of both sexes over 40 y of age without other diseases included in this prospective clinical trial. Forty (40) patients were treated with amlodipine (5 mg/day) and forty-one (41) patients were treated with perindopril (4 mg/day). After one month of taking both drugs, blood pressure was measured in the supine position with a standard mercury sphygmomanometer in the morning. Results: Amlodipine and perindopril groups were having almost similar characteristics at the beginning of the study. There was significantly decrease insystolic blood pressure (sBP) throughout the study period in the amlodipine group (p≤ 0.05) but not in the perindopril group. The efficacy of amlodipine over perindopril on systolic blood pressure and diastolic blood pressure (dBP) was significant (p≤ 0.001 for sBP and p≤ 0.05 for dBP). Conclusion: It may be concluded that the antihypertensive efficacy of amlodipine was superior when compared to perindopril.